2011
DOI: 10.1007/s00125-011-2102-z
|View full text |Cite|
|
Sign up to set email alerts
|

Recombinant human prolactin promotes human beta cell survival via inhibition of extrinsic and intrinsic apoptosis pathways

Abstract: Aims/hypothesis Transplantation of pancreatic islets constitutes a promising alternative treatment for type 1 diabetes. However, it is limited by the shortage of organ donors. Previous results from our laboratory have demonstrated beneficial effects of recombinant human prolactin (rhPRL) treatment on beta cell cultures. We therefore investigated the role of rhPRL action in human beta cell survival, focusing on the molecular mechanisms involved in this process. Methods Human pancreatic islets were isolated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 56 publications
2
59
0
11
Order By: Relevance
“…Western blot analysis of human islets treated with hPRL for 24 h did not show a significant increase in the ratio of BCLXL:actin compared with vehicle-treated human islets (0.88±0.2 vs. 0.67±0.3, respectively). PRL is known to activate p-STAT5 in human islets [28] and, using our findings in rodent islets (Fig. 5), we hypothesised that STAT5 activation is likely to be involved in the prosurvival effects of lactogens in human beta cells.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Western blot analysis of human islets treated with hPRL for 24 h did not show a significant increase in the ratio of BCLXL:actin compared with vehicle-treated human islets (0.88±0.2 vs. 0.67±0.3, respectively). PRL is known to activate p-STAT5 in human islets [28] and, using our findings in rodent islets (Fig. 5), we hypothesised that STAT5 activation is likely to be involved in the prosurvival effects of lactogens in human beta cells.…”
Section: Resultsmentioning
confidence: 59%
“…Previously, we found that lactogens can protect rodent beta cells against other cell death inducers including STZ and DEX [23][24][25][26]. Recent findings show that PRL also protects human beta cells against different cell death inducers, including cytokines, hydrogen peroxide and serum-starvation [28,29]. Therefore, together, these studies clearly suggest that lactogens are prosurvival factors for the beta cell, in rodents and humans, against varied cell death inducers that are important in type 1 and 2 diabetes and islet transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highest rate of beta cell proliferation [21,22] Increased insulin secretion, which is, in part, due to transient insulin resistance [44,45] Doubling of beta cell mass by 5 years of age [22] Several-fold increase in beta cell mass from birth to adulthood [50,51] Increase in beta cells per islet and in islet size [51,52] Evidence of beta cell neogenesis and a regenerative response in diabetes [53] Mature beta cells are sensitive to perturbations in cell cycle control [60] Pro-survival effects of lactogen hormones on beta cells [99,100] but not alpha cells [102] Cytoprotective effect of GLP-1 on beta cells [104] GIP stimulates glucagon secretion [113], while GLP-1 inhibits secretion [112] Increase in beta cell mass reported in obesity [119] Reduction in beta cell mass and relative increase in alpha cell mass in diabetes [74] Decline in beta cell function; decline in beta cell replication Beta cell mass remains relatively constant in healthy humans [121] No major alterations in beta cell size [120] Beta cell apoptosis is low and remains constant throughout life [21] In diabetes: Mitochondrial dysfunction, oxidative stress, ER stress and accumulation of intermediate-sized amyloid particles [127] Neonatal age Puberty Adolescence Adulthood Old age diabetes coupled with high expression of IL-6 receptors on alpha cells suggest that this cytokine could contribute to the increased alpha cell mass observed in diabetes [88]. This notion is supported by fasting hypoglucagonaemia and an inability of mice lacking IL-6 to increase their alpha cell mass.…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 99%
“…These hormones stimulate beta cell proliferation in isolated islets, and beta cell mass is reduced by up to 42% in receptor-deficient mice [98]. It has recently been demonstrated that the pro-survival effects of lactogens are mediated by protection against apoptotic pathways controlled by members of the BCL2 gene family in human beta cells [99] and against glucolipotoxicityinduced cell death via Janus kinase 2 (JAK2)/signal transducer and activator of transcription 5 (STAT5) signalling [100]. While in vitro studies have demonstrated that human somatomammotropin stimulates glucagon release [101], in vivo studies in both rats and humans suggest that pregnancy does not affect alpha cell function [102] and that alpha cells might not be involved in the increased insulin demand in response to insulin resistance during normal human pregnancy [103].…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 99%